(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
The process of forming a sense of responsibility in preschool children must be successfully carried out in the conditions of cooperation between educators and parents. A preschooler must be aware of his capabilities and individual characteristics, be able to communicate with adults and peers, show empathy and cooperation, be able to make decisions in non-standard situations and be responsible for